Ultrasound Guided Fine Needle Aspiration Biopsy in Renal Tumors - Tjahjodjati Tjahjodjati; Joko Pitoyo (Faculty of Medicine Universitas Padjadjaran, 2015)
Objective: To assess the sensitivity and specificity of ultrasound guided fine needle aspiration biopsy (FNAB) in renal tumors.Methods: A diagnostic study was performed on 23 patients with renal tumors who visited the Urology Division, Department of Surgery, Dr. Hasan Sadikin General Hospital from January 2011 to August 2012. First time ultrasound guided was performed to the patients before nephrectomy. Renal tissues that were obtained from both procedures were examined histopathologically, and the result from nephrectomy was used as the gold standard. Analysis was conducted by measuring the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the ultrasound guided FNAB. Results: The results showed that the sensitivity value of ultrasound guided FNAB was 85.71%, with 50% specificity, 94.74% PPV and 25% NPV. From 23 patients, only 2 patients had hematoma. Conclusions: Ultrasound guided FNAB is sufficiently sensitive with a fair specificity for diagnosing renal tumors and is safe for patients.Keywords: Renal tumor, sensitivity, specificity, ultasound guided FNAB DOI: 10.15850/ijihs.v3n1.401